Effect of ON and OFF Axis Open Hole Tensile Testing of GFRP/Epoxy Composites - Sunith Babu Loganathan; Ashok Kumar Krishnappa; Jaya Christiyan Kumaravelu Grace Jesu Bai; Ritin Pavirala; Rajesh Mathivanan (Mechanics of Advanced Composite Structures)
Composites are widely used for different applications in engineering mainly due to their tailored benefits, durability, reduced maintenance, and enhanced performance. GFRP is a synthetic material that has revolutionized the aerospace industry, offering a high strength-to-weight ratio, fuel efficiency, and enhanced performance for advanced applications. In structures like aircraft components, holes or notches are often present due to design requirements or secondary joining processes through rivets or bolted connections, which leads to wear and tear. Further, how these materials behave under tensile loads near these openings is critical for ensuring the safety and reliability of such structures. In the present study, GFRP/Epoxy composite laminates are subjected to open hole tensile test under ON and OFF axis orientations. The effect of loading under different sequences was studied. The nature of failure near the hole region was reviewed and presented. It is noted that the dominant failure was LGM type under the ON-axis and different under the OFF-axis which is not limited to shear failure, interlaminar delamination, and mixed mode failures. These trends are noted for different hole dia, namely 6,9,12 and 18mm. The study also presents the nature of the stress-strain curve for both configurations. The OFF-axis specimens displayed a non-linear behavior to failure as compared to the On-axis type. While, the on-axis specimens showed a marked reduction in peak load and tensile strength as hole dia increased with reductions up to 65.23% and 63.57%, respectively relative to hole-less specimens. The inclined failure in off-axis specimens varied between 500 - 550. Further, the damage tolerance in OFF-axis samples was higher as compared to ON-axis specimens.